The effects of hydrotherapy on athletic ability in children with cerebral palsy: A systematic review and meta-analysis - Ye Tao; Ziyi Cao; Min-Chul Shin; Meijia Chen; Shuaiju Han (PLoS ONE, 2025)
Background Cerebral palsy (CP) is a disability caused by brain malformations or injuries occurring from conception to infancy. Hydrotherapy is a popular treatment for children with cerebral palsy and other neuromotor disorders. Despite evidence supporting the efficacy of hydrotherapy for treating children with cerebral palsy, there remains controversy regarding its effectiveness over different follow-up periods and in comparison with other physical therapy methods. Objective To compare the effects of hydrotherapy on gross motor abilities, fine motor functions, balance, and muscle tone in children and adolescents with cerebral palsy, and to assess evaluate efficacy across different age stages and treatment durations. Methods This meta-analysis was registered with PROSPERO (registration number CRD42024535838). Literature searches were conducted in databases including CNKI, VIP, WanFang, Web of Science, PubMed, Embase, and the Cochrane Library starting from June 2024. Randomized controlled trials (RCTs) that assessed the effects of hydrotherapy on gross motor functions, fine motor functions, balance, and muscle tone in children and adolescents with cerebral palsy were included. RCTs were evaluated for quality using the Cochrane risk of bias tool. Outcomes were analyzed by calculating mean difference (MD) or standardized mean difference (SMD) along with their 95% confidence intervals (CIs). Results Sixteen studies were included, assessing the impact of hydrotherapy compared to conventional care on gross motor functions in children and adolescents with cerebral palsy. The findings indicated that hydrotherapy significantly improved gross motor functions [SMD = 0.41, 95% CI = 0.15–0.68, I2 = 59.5%, p < 0.05], with consistent effects observed in children aged ≤6 years [SMD = 0.42, 95% CI = 0.16–0.68, I2 = 38.2%, p < 0.05] and those aged >6 years [SMD = 0.43, 95% CI = 0.22–0.63, I2 = 59.5%, p < 0.05]. Subgroup analysis based on intervention duration revealed that programs lasting more than 10 weeks were associated with significant improvements [SMD = 0.48, 95% CI = 0.31–0.66, I2 = 65.1%, p < 0.05], whereas no significant effects were found in interventions lasting 10 weeks or less [SMD = 0.14, 95% CI = –0.26–0.53, I2 = 35.6%, p > 0.05]. Hydrotherapy demonstrated a certain positive effect on fine motor functions [SMD = 0.78, 95% CI = 0.46–1.10, I2 = 46.4%, p > 0.05].In contrast, no statistically significant improvements were observed in balance [SMD = 0.64, 95% CI = –0.05–1.34, I2 = 80.7%, p > 0.05] or muscle tone [SMD = –0.45, 95% CI = –0.98–0.07, I2 = 58.2%, p > 0.05]. Conclusion The results indicate that hydrotherapy is more effective than conventional treatment in improving gross motor functions in children and adolescents with cerebral palsy, with consistent benefits observed across different age groups and in interventions of longer duration. Hydrotherapy also showed a positive trend in enhancing fine motor functions, although no significant improvements were observed in balance or muscle tone.